Pintar Finansial dengan Fintech: Membangun Ketahanan Keuangan Usaha Mikro Kecil dan Menengah Melalui Program Literasi untuk Mencegah Korban Pinjol - Aisah, Nurul; Rizkiawan, Ilham Karin; Hermansyah, Doni (LPPM Universitas Bumigora, 2024)
The aim of this community service is to increase MSMEs' understanding of Fintech by providing literacy to build the financial resilience of MSMEs so that they do not get caught in Illegal Online Loan fraud. Adaptation to technological developments requires people to be smart about their finances. The partners of this service are the MSMEs of Gergunung Klaten Village, with 41 participants. The main problem faced by MSME partners in Gergunung Klaten Village is the lack of technological and financial knowledge among Gergunung Klaten Village MSMEs and the frequent offers of online loans, even though their knowledge, especially regarding FinTech, is still low, so they have the potential to become victims of illegal loans. This community service is focused on fintech literacy, which plays an important role in efforts to mitigate the risk of Online Loan victims. Through a service approach that involves counseling and providing clear and accurate information, MSME services and development can be empowered to make smarter financial decisions and be aware of the risks and benefits of fintech services, especially in the case of Online Loan. The methods used are counseling, prevention of illegal borrowing, and services, as well as developing the needs of MSMEs by simulating the use of fintech. The results of this service are able to increase fintech literacy and public awareness of the dangers of illegal Online Loan. With a better understanding of fintech and Online Loan, people, especially MSMEs, have the tools to make smarter financial decisions and reduce the risk of fraud. This effort contributes to the formation of a society that is more financially empowered and smarter when making transactions via financial technology platforms.